Caveat emptor: Foreign aid and entrepreneurship - Tomi Ovaska; Ryo Takashima (Economies, 2020)
In the last 60 years, the results of development aid have been mixed. Thus far, it has been mostly the aid recipient countries, which have been held responsible for aid's shortcomings. That focus is misplaced, however, since the donor countries, through development aid, also export some of their own institutions and values to the recipient countries affecting the recipients' rate of entrepreneurship and income. This study demonstrates how donor countries vary widely in both the type and quality of their institutions and values, leading to diverging economic outcomes. The results indicate that recipient countries should pay serious attention to who their development partner is. In particular, recipients would want to avoid aid from low institutional quality donors with perceived anti-market attitudes. Finally, it is argued that development aid might become more efficient if it moved away from the bilateral, towards the multilateral, mode.
Keywords: E61; F35; F55; F63; H11; 330; aid donors; aid recipients; attitudes; bilateral aid; development aid; economic freedom; entrepreneurship; foreign aid; institutional quality; multilateral aid; TEA; values